Proteomics of specific treatment-related alterations in Fabry disease: a strategy to identify biological abnormalities - Moore, David F.; Krokhin, Oleg V.; Beavis, Ronald C.; Ries, Markus; Robinson, Chevalia; Goldin, Ehud; Brady, Roscoe O.; Wilkins, John A.; Schiffmann, Raphael (Proceedings of the National Academy of Sciences of the United States of America, 2007)
Fabry disease is inherited as an X-linked disorder secondary to deficiency of α-galactosidase A, resulting in abnormal metabolism of substances containing α-d-galactosyl moieties. As a consequence, a multisystem disorder develops, culminating in strokes, progressive renal, and cardiac dysfunction. Signs and symptoms of Fabry disease become manifest in childhood, but diagnosis is often delayed. Thirteen children with Fabry disease (age range, 6.5-17 years) were studied as part of a 6-month open-label study of enzyme replacement therapy (ERT) with agalsidase alfa. Paired serum samples were drawn at the start of the study and after 6 months of ERT. Global protein changes in paired samples were compared by using differential stable isotope labeling of peptide lysine residues with O-methylisourea and subsequent nanoHPLC-tandem MS. Statistically significant decreases were observed for five proteins following ERT: α2-HS glycoprotein, vitamin D-binding protein, transferrin, Ig-α-2 C chain, and α-2-antiplasmin. The presence of low levels of α-2-antiplasmin and plasminogen was confirmed by alternate means in 34 consecutive patients, including four of five ERT-naïve subjects. Decreased α-2-antiplasmin was associated with a parallel increase in circulating VEGF. Soluble VEGF receptor-2 was significantly elevated in plasma of patients compared with pediatric controls and decreased with ERT. These results suggest previously unknown abnormalities of fibrinolysis and angiogenesis factors in Fabry disease. We demonstrated the feasibility of identifying treatment-specific alterations in a small number of subjects that point to previously unsuspected disease-related biological abnormalities.
Gesehen am 15.05.2019